Effect of fundus tracking on structure–function relationship in glaucoma. Issue 12 (2nd March 2020) - Montesano, Giovanni; Rossetti, Luca M; McKendrick, Allison M; Turpin, Andrew; Fogagnolo, Paolo; Oddone, Francesco; Lanzetta, Paolo; Perdicchi, Andrea; Johnson, Chris A; Brusini, Paolo; Garway-Heath, David F; Crabb, David P
Abstract : Aims: To investigate the effect of fundus tracking perimetry on structure–function relationship in glaucoma. Methods: Perimetric data were acquired with the Humphrey Field Analyzer (HFA) and the Compass fundus perimeter (CMP, equipped with fundus tracking). We included data from 696 eyes from 360 healthy people and 711 eyes from 434 patients with glaucoma from the original study, for which the circumpapillary retinal nerve fibre layer optical coherence tomography scan (Cp-RNFL) was available. We explored the structure–function relationship using both global indices (mean deviation and average Cp-RNFL thickness loss) and anatomically defined visual field clusters comparing the R 2 values from mixed-effect models. We then measured the diagnostic ability of a combined Structure Function Index (SFI) using perimetric data from either perimeter. The comparisons were based on partial receiver operating characteristic curves with a minimum specificity of 75% and their areas under the curve. Results: The R 2 for the global structure–function relationship was 0.50 for the CMP and 0.48 for the HFA. When visual field clusters were included in the model, the R 2 was 0.29 for CMP and 0.30 for HFA. Overall, the discrimination ability of the SFI was not significantly higher than the Cp-RNFL for either the CMP (p=0.07) or the HFA (p=0.14). However, it was significantly better in eyes with perimetric damage (p<0.001), in which the CMP-SFI performed significantly better than the HFA-SFI (p=0.03). Conclusions: Structure–function relationship is similar between the two perimeters. Fundus tracking might improve discrimination ability with a combined SFI. Trial registration number: ISRCTN13800424 .